Efficacy and Safety of Eculizumab in Enteroaggregative E. coli Associated Hemolytic Uremic Syndrome - Ratna Acharya; William L. Clapp; Kiran Upadhyay (MDPI AG, 2024)
Background. Hemolytic uremic syndrome (HUS) may present atypically without the full triad of classical HUS. Eculizumab has been shown to be efficacious in complement-mediated atypical HUS and some cases of Shiga-toxin (ST) associated HUS. We report the utility of eculizumab in enteroaggregative E. coli (EAEC) associated HUS. Case summary. A female toddler presented with hemolytic anemia, oliguric acute kidney injury (AKI) without thrombocytopenia, and peripheral schistocytes. The stool examination for ST was negative but positive for EAEC. She required several hemodialysis sessions and received one dosage of eculizumab with rapid reversal of AKI and hemolytic markers. A kidney biopsy revealed acute tubular injury and segmental glomerular basement membrane splitting. Genetic testing was negative for complement mutations or deficiencies. A follow-up six months later showed persistently normal renal function and hematological markers. Conclusion. The clinical and histological manifestations of non-ST-associated diarrheal HUS and the role of eculizumab in this condition warrant future larger studies.